1979
DOI: 10.1073/pnas.76.5.2442
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma development in mice and humans: diversity of initiation is followed by convergent cytogenetic evolution.

Abstract: Human B cell lymphoma and murine T cell leukemia can be initiated by several agents. The present paper formulates some thoughts on the role of cytogenetic changes in the subsequent neoplastic process. Initiation creates long-lived preneoplastic cells. In some respects, they are comparable to in vitro-transformed ("immortalized") cell lines that maintain a diploid karyotype and are not tumorigenic in vivo. The development of a tumorigenic ("autonomous") clone is dependent on additional changes at the genetic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
70
0
3

Year Published

1980
1980
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(77 citation statements)
references
References 74 publications
(39 reference statements)
4
70
0
3
Order By: Relevance
“…Note that such effects cannot be detected in bacterial assays. It has been shown repeatedly that clastogenic and aneugenic effects in somatic cells are associated with the development of cancer [32][33][34][35] and a number of earlier studies have shown that the MN assay with exfoliated cells is an appropriate tool to monitor cancer risks in humans caused by exposure to environmental factors or inherited genomic instability. 10,14,16 -18 Therefore, the present findings suggest that khat chewing may cause cancer in the oral cavity or other parts of the upper digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…Note that such effects cannot be detected in bacterial assays. It has been shown repeatedly that clastogenic and aneugenic effects in somatic cells are associated with the development of cancer [32][33][34][35] and a number of earlier studies have shown that the MN assay with exfoliated cells is an appropriate tool to monitor cancer risks in humans caused by exposure to environmental factors or inherited genomic instability. 10,14,16 -18 Therefore, the present findings suggest that khat chewing may cause cancer in the oral cavity or other parts of the upper digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic changes of these two genes were also found in human hematopoietic malignancies (Sun et al, 1999;Bernard et al, 2001;Itoyama et al, 2001;Yagi et al, 2002;MacLeod et al, 2003;Nagel et al, 2003;Bezrookove and van Zelderen-Bhola, 2004;Przybylski et al, 2005). Studies in other laboratories implicated several genes in the lymphoma development such as Myc, Notch1 and PTEN (Klein, 1979;Graham et al, 1985;Ellisen et al, 1991;Mao et al, 2003;Lin et al, 2006;O'Neil et al, 2006). On the other hand, mutation frequencies of mostly delineated ras and p53 genes were low in radiogenic thymic lymphomas Brathwaite et al, 1992).…”
Section: Introductionmentioning
confidence: 94%
“…In addition to immortalization of B lymphocytes, oncogenesis by EBV in Burkitt's lymphoma requires chromosomal transformation [2]. Hanto et al [6] describe the karyotypes of six lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…The precise role of the virus in carcinogenesis is unclear, although in Burkitt's lymphoma the importance of viral transformation of infected B lymphocytes and chromosomal translocations has been emphasized [2]. It is even less clear in lymphomas and lymphoproliferative lesions arising in immuno-compromised patients, where the immunopathology may not be uniform and where chromosomal studies are largely lacking.…”
Section: Introductionmentioning
confidence: 96%